The Effect of Topical Administration of Asi on Care and Duration of Immunal Cord Removal - Harahap, Novy Ramini; Nurrahmaton, Nurrahmaton; Syari, Mila; Hasanah, Fitri Husratul (Jurnal MID-Z (MIDWIFERI ZIGOT), 2024)
Umbilical Cord Care can also be interpreted as the care of the umbilical cord in a clean state, with efforts to minimize exposure to dust and dirt to prevent infection. Proper and correct umbilical cord care has a positive impact, especially on infants. If we care for the umbilical cord properly, it will also facilitate a quick cord detachment. The objective of this research is to determine the frequency of umbilical cord care and the duration of cord detachment before and after the administration of topical breast milk, the average duration of care, and the influence of topical breast milk administration at Klinik Pratama Shanty in 2023. The research design employed is a "pre-experiment" with a twogroup pretest and posttest design involving both a control group, which does not receive any treatment, and an intervention group, which receives treatment. The data for this study was collected by the researcher using observation sheets, and the collected data was subsequently tabulated. In this research, the sample for the administration of topical breast milk to newborns consisted of 20 respondents, divided into two groups: the intervention group and the control group, based on inclusion and exclusion criteria. The results of the normality test for the data using the Shapiro-Wilk test indicated a p-value (significance) of 0.02, which is less than 0.05. Therefore, the null hypothesis (Ho) is accepted, suggesting that the data is not normally distributed when topical breast milk is not used at Klinik Pratama Shanty in 2023.